2020
DOI: 10.1039/d0ra05532h
|View full text |Cite
|
Sign up to set email alerts
|

Fused multicyclic polyketides with a two-spiro-carbon skeleton from mangrove-derived endophytic fungus Epicoccum nigrum SCNU-F0002

Abstract: A pair of uncommon fused multicyclic polyketides, (±)-isoepicolactone and one new isobenzofuranone monomer, together with four other known biosynthetically related compounds were isolated from the fermentation of fungus Epicoccum nigrum SCNU-F0002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…8 | Additional examples for anticipated natural products and suspected natural products awaiting cofirmation. a | iso-epicolactone (92) [75,76] , (+)brevianamide Y (93), [77][78][79] (±)-desoxyisobruceol (94) [80][81][82][83] , and (-)-prehalenaquinone (95) [84] are additional examples for molecules that were synthesized in the laboratory prior to their isolation. b | Cases of anticipated natural products that await isolation from natural sources: 8-epi-isoaplydactone (96), [85] dia-angiopterlactone B (97), [86] biyouyanagin C (98), [87] epi-pycnanthuquinone C (99), [88] 8-epi-homodimericin A (100), [89] intricarene side-product (101), [90] protected dia-millingtonine (102) [91] , diaincargranine B aglycone (103) [92] , diastereomer towards neonectrolides (104) [93] , preuisolactone precursor (105) [94] , nuphar alkaloid isomer (106) [95] , side-product towards (+)-norcembrene 5 (107) [96] , monolomaiviticin A (108) [97] , 2-epilankacyclinol (109) [98] , 3,7-epi-massadine (110) [99] , santarubin S (111) [100] , epiguajadial B (112) [101] , Δ 23,24 -perovskone (113) [102] , epi-pungiolide A (114) [103] , and iso-aspergilasine A (115) [104] .…”
Section: Discussionmentioning
confidence: 99%
“…8 | Additional examples for anticipated natural products and suspected natural products awaiting cofirmation. a | iso-epicolactone (92) [75,76] , (+)brevianamide Y (93), [77][78][79] (±)-desoxyisobruceol (94) [80][81][82][83] , and (-)-prehalenaquinone (95) [84] are additional examples for molecules that were synthesized in the laboratory prior to their isolation. b | Cases of anticipated natural products that await isolation from natural sources: 8-epi-isoaplydactone (96), [85] dia-angiopterlactone B (97), [86] biyouyanagin C (98), [87] epi-pycnanthuquinone C (99), [88] 8-epi-homodimericin A (100), [89] intricarene side-product (101), [90] protected dia-millingtonine (102) [91] , diaincargranine B aglycone (103) [92] , diastereomer towards neonectrolides (104) [93] , preuisolactone precursor (105) [94] , nuphar alkaloid isomer (106) [95] , side-product towards (+)-norcembrene 5 (107) [96] , monolomaiviticin A (108) [97] , 2-epilankacyclinol (109) [98] , 3,7-epi-massadine (110) [99] , santarubin S (111) [100] , epiguajadial B (112) [101] , Δ 23,24 -perovskone (113) [102] , epi-pungiolide A (114) [103] , and iso-aspergilasine A (115) [104] .…”
Section: Discussionmentioning
confidence: 99%
“…49 As the isomer of benzofuran, compounds of isobenzofuran and its derivatives include 46 metabolites from mangroveassociated fungi. The Epicoccum strain was the source of the isobenzofuran, including 5,6-dihydroxy-7-methoxy-4-methylisobenzofuran-1(3H)-one (282), 49 (+)-epicoccone C ( 283), (À)-epicoccone C ( 284), epicoccone D-F (285-287), 158,159 epicolactone A (288), 158 and a pair of polyketides (AE)-isoepicolactone (289 and 290) with a two-spiro-carbon skeleton. 159 From the Mycosphaerella strain, a new isobenzofuranone dimer, dibefurin B (291), and an isobenzofuranone monomer 292 were isolated.…”
Section: Reviewmentioning
confidence: 99%
“…The Epicoccum strain was the source of the isobenzofuran, including 5,6-dihydroxy-7-methoxy-4-methylisobenzofuran-1(3H)-one (282), 49 (+)-epicoccone C ( 283), (À)-epicoccone C ( 284), epicoccone D-F (285-287), 158,159 epicolactone A (288), 158 and a pair of polyketides (AE)-isoepicolactone (289 and 290) with a two-spiro-carbon skeleton. 159 From the Mycosphaerella strain, a new isobenzofuranone dimer, dibefurin B (291), and an isobenzofuranone monomer 292 were isolated. 160 The Ascomycota strain yielded three new isobenzofuran derivatives, ascomfurans A-C (293-295).…”
Section: Reviewmentioning
confidence: 99%
“…Heterospirocyclic compounds widely exist in various pharmacological agents and agricultural products, and can be used as anticancer, anticonvulsant, and antimicrobial agents. 49 Wang et al reported the synthesis of spiroox-azine derivatives through immobilized CALB-initiated multicomponent reaction from nitrostyrene, cyclohexanone, p-nitrobenzaldehyde, and acetamide substrates, enabling six C-C/C-N bonds and two heterocycles in one-pot operation (►Scheme 17A). 50 When p-nitrobenzaldehyde was replaced by other aromatic aldehydes, the yield was very low.…”
Section: Synthesis Of Other Heterocyclic Compoundsmentioning
confidence: 99%